Análise morfofuncional de fagócitos do sangue de ema (Rhea americana) em cativeiro - Rodrigues, Luiz Carlos Toledo (2006)
The Ema (Rhea American ) is a bird in extinction. It is created in captivities, which fact causes some problems related to the handler, like physiologic stress and hormonal interaction, influencing on the immunological answer. This change can act on the activation of mononucleos and polimophonucleos, promoting the liberation of anion-superóxido. The aim of this work is to value the morphology and the cellular activation of heterophilus from emas blood (male and female) with the hormone melatonin and the Escherichia coli. Were collected 20 samples of blood (10 males and 10 females) of animals from Ambiental Development Centre of Companhia Brasileira de Metalurgia e Mineiração. The separation of cells took place through the method gradient of density Ficoll Paque and sedimentation by dextran (Sigma). For the liberation of ânion-superóxido were used the method Acridine Orange. With the hormone melatonin, were checked some different statistics where males have more activation (16,5 + 1,1) than the females (14,1 + 0,5) (p<0,05). The heterophilus are big and have a kind of spherical, oval or irregular form with granules of several aspects. Notice that the phagocyte in the Ema s blood have phagocytec activity for Escherichia Coli, and there wasn t a meaningful difference between the cells of males and females. The index of microbicidal was also similar between the types of phagocyte with values up to 60%. We can conclude that the functional activation of heterophilus from ema s blood by agents imunomodulatory depend on the sex and this cells can be consider an important mechanism of defense to this animals, up against the bacterial infections.